The Effect of Three Different Dressing Materials on Pain Relief of Symptomatic Teeth. Randomized Clinical Trial (Mustansiria Dental Journal, 2024)
Different types of materials were used in aim to reduce pain and to alleviate of symptoms. These materials have been used for decades like formocresol, cresatin, eugenol, CMCP and iodine-potassium because of their antiseptics and germicidal effects that should reduce the pain. In recent years the introduction of pulpotec material that contain both formalaldehyde and dexamethasone acetate may provide both antiseptics and sedative effect of steroids.The aim of this study is to evaluate the use of pulpotec and compare it with other most common materials used in pulpotomy as emergency treatment dressings (camphorated monochlorphenol and eugenol). Materials and methods: sixty patients (26 meals and 45 females) were included in this study after their approval to the treatment protocol. The three materials were applied. All the participants of the three groups recalled after eight hours, twenty-four hours and seventy-two hours. Results and conclusion: the pulpotec group shows complete relief of pain 100% will the other two groups show mild to severe pain after one to three days. On conclusion, steroids can be used locally to provide alleviation of pain in symptomatic teeth due to their anti-inflammatory effect and reduce their side effect. That will diminish the use of systemic antibiotics.